2011
DOI: 10.1111/j.1600-0625.2011.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

A broad-spectrum sunscreen prevents UVA radiation-induced gene expression in reconstructed skin in vitro and in human skin in vivo

Abstract: The efficacy of sunscreens to protect against ultraviolet (UV) A radiation is usually assessed by measuring erythema formation and pigmentation. The biological relevance of these endpoints for UVA-induced skin damage, however, is not known. We therefore carried out two complementary studies to determine UVA protection provided by a broad-spectrum sunscreen product at a molecular level by studying UVA radiation-induced gene expression. One study was performed on human reconstructed skin in vitro with a semi-glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…We previously showed that UVA spectrum, including UVA2 and UVA1, can induce proinflammatory mediators in reconstructed skin [19]. We now show that UVA1 exposure per se induced an increase in the level of inflammation markers, such as IL6, CCL20 and CSF2 (GM-CSF) genes and proteins as well as IL1A, IL1B, IL8, PTGS2 (COX-2), TNFAIP3, ICAM1 and LIF genes.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We previously showed that UVA spectrum, including UVA2 and UVA1, can induce proinflammatory mediators in reconstructed skin [19]. We now show that UVA1 exposure per se induced an increase in the level of inflammation markers, such as IL6, CCL20 and CSF2 (GM-CSF) genes and proteins as well as IL1A, IL1B, IL8, PTGS2 (COX-2), TNFAIP3, ICAM1 and LIF genes.…”
Section: Discussionmentioning
confidence: 60%
“…The three dimensional architecture of the model allows us to take into account UV penetration properties depending on wavelength [16]. Using this model, we have previously reproduced the major epidermal alterations induced by UVB as well as identified direct dermal damage occurring after UVA (including UVA2 and UVA1) through ROS generation, dermal fibroblast apoptosis, matrix metalloproteinase (MMP) release and modulation of the expression of genes related to extracellular matrix homeostasis [17][19].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, 3 major proteins involved in ECM remodeling were significantly induced: 2 matrix metalloproteinases, MMP1 and MMP3 and SERPINB2, one of the major inhibitor of the Plasminogen Activator system. The modulation of these markers following UVA exposure has previously been described [5,6]. We report that, even very low doses of DUVR can also affect the expression of genes that encode proteins involved in ECM composition, maturation and remodeling, that occurs during photoaging process.…”
Section: Journal Of Dermatological Sciencementioning
confidence: 71%
“…Sunscreen pre-application abrogated these effects or reduced them significantly. This revealed a very high photoprotective activity of the sunscreen that could be evidenced using an unsupervised clustering analysis or a gene by gene comparison approach [40] [ Figure 6]. This data indicated that a broad-spectrum sunscreen Figure 6: Heat map of gene expression in reconstructed skin exposed to 30 J/cm 2 UVA.…”
Section: Protective Effects Of Well-balanced Sunscreensmentioning
confidence: 91%
“…[37][38][39][40] Since the in vitro model has a horny layer, it is possible to apply the products topically on skin surface, thus mimicking real life conditions. The protecting effects against UV-induced epidermal or dermal damage in reconstructed skin model can be evaluated at various time points after exposure.…”
Section: Protective Effects Of Well-balanced Sunscreensmentioning
confidence: 99%